Pengaruh Kepuasan Transaksi Online dan Kepercayaan Terhadap Sikap Konsumen pada E-Commerce (Studi Kasus Pembelian Produk Lazada.Co.Id Pada Mahasiswa di Kota Yogyakarta) - Indratno, Diana Leli; Ramaini, Siti (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2018)
This research aims to determine whether online transaction satisfaction and trust influence on consumer attitudes on e-commerce (Case Study of purchasing products Lazada.co.id on students in the city of Yogyakarta). This study used a sample of 100 respondents selected by Non Probability Sampling technique. Using Multiple Linear Regression analysis methodThe results of multiple linear regression test showed that the variable of satisfaction and trustworthiness significantly influence consumer attitudes of e-commerce users Lazada.co.id on students in the city of Yogyakarta. Hypothesis test shows t test (partial) that the satisfaction effect is proved (2,989)(1,660) with significant level 0,004 which value is less than 0,05, and influence belief is proved (4,283)(1,660) with significance level 0,000 whose value is below 0.05. Hypothesis test shows that the variable of satisfaction and trust significantly influence consumer attitudes of e-commerce users Lazada.co.id to students in Yogyakarta city is evidenced by the value of (15.298)(3.090) with a significance level of 0.000 value is below 0.05. Of the two independent variables, the confidence variable which is more dominant variable to consumer attitudes of e-commerce users Lazada.co.id to students in Yogyakarta city is evidenced by the standard Î² 0.359 â‰¥ 0.312 with significant value 0.000 â‰¤ 0.004.Â